PERAN CORPORATE GOVERNANCE DALAM MENGENDALIKAN TAX AVOIDANCE: SYSTEMATIC LITERATURE REVIEW - Khadijah, Jihan Nur (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to conduct a systematic review of the influence of corporate governance mechanisms on tax avoidance practices across various countries. Articles were collected using Publish or Perish for Scopus-indexed and other relevant databases. The methodology used in this review is a systematic literature review, resulting in 36 articles on corporate governance and tax avoidance, selected through the PRISMA elimination process. The findings indicate that corporate governance mechanisms have varying effects on tax avoidance practices—some reduce it, others increase it, while some show no significant effect. The results of this study can provide valuable guidance for companies in improving their tax compliance and offer recommendations to stakeholders and policymakers for new approaches toward promoting more responsible tax behavior.